Prolonged health worker strikes in Kenya- perspectives and experiences of frontline health managers and local communities in Kilifi County - Dennis Waithaka; Nancy Kagwanja; Jacinta Nzinga; Benjamin Tsofa; Hassan Leli; Christine Mataza; Amek Nyaguara; Philip Bejon; Lucy Gilson; Edwine Barasa; Sassy Molyneux (BMC, 2020)
Abstract Background While health worker strikes are experienced globally, the effects can be worst in countries with infrastructural and resource challenges, weak institutional arrangements, underdeveloped organizational ethics codes, and unaffordable alternative options for the poor. In Kenya, there have been a series of public health worker strikes in the post devolution period. We explored the perceptions and experiences of frontline health managers and community members of the 2017 prolonged health workers' strikes. Methods We employed an embedded research approach in one county in the Kenyan Coast. We collected in-depth qualitative data through informal observations, reflective meetings, individual and group interviews and document reviews (n = 5), and analysed the data using a thematic approach. Individual interviews were held with frontline health managers (n = 26), and group interviews with community representatives (4 health facility committee member groups, and 4 broader community representative groups). Interviews were held during and immediately after the nurses' strike. Findings In the face of major health facility and service closures and disruptions, frontline health managers enacted a range of strategies to keep key services open, but many strategies were piecemeal, inconsistent and difficult to sustain. Interviewees reported huge negative health and financial strike impacts on local communities, and especially the poor. There is limited evidence of improved health system preparedness to cope with any future strikes. Conclusion Strikes cannot be seen in isolation of the prevailing policy and health systems context. The 2017 prolonged strikes highlight the underlying and longer-term frustration amongst public sector health workers in Kenya. The health system exhibited properties of complex adaptive systems that are interdependent and interactive. Reactive responses within the public system and the use of private healthcare led to limited continued activity through the strike, but were not sufficient to confer resilience to the shock of the prolonged strikes. To minimise the negative effects of strikes when they occur, careful monitoring and advanced planning is needed. Planning should aim to ensure that emergency and other essential services are maintained, threats between staff are minimized, health worker demands are reasonable, and that governments respect and honor agreements.